Ab initio calculation of the proton transfer reaction rate coefficients to volatile organic compounds related to cork taint in wine. (3rd August 2020) - Bhatia, Manjeet; Biasioli, Franco; Cappellin, Luca; Piseri, Paolo; Manini, Nicola
Abstract: We compute the proton transfer rates to a range of volatile organic compounds (VOCs) related to cork taint in wine. These rates are useful to support quantification in proton‐transfer‐reaction mass spectrometry (PTR‐MS) and in selected‐ion flow‐tube mass spectrometry (SIFT‐MS). We apply the average dipole orientation theory and the parameterized trajectory method to evaluate the rate coefficients for proton transfer occurring in ion–molecule collision, from both H3 O + and NH 4 + to the VOCs. The main input ingredients for these methods are the electric dipole moment and polarizability of the VOC molecules, which we evaluate by means of quantum chemical calculations based on density functional theory. We provide new data for proton transfer rate coefficients of compounds responsible for cork taint and off‐flavor in wine such as chloroanisoles, bromoanisoles, methylisoborneol, guaiacol, and terpenes.